(3GdeONd dOQGSI GdYbjOI GdESdGejI Ydi ePgH Cgd GdSfI hGdLeGYI (B/s - (3GdHQjcGf, EHQGgje Hf eMeO Hf YHO Gddgs 1375-1429 (3gLQjs ((3GdOeGe (B- (3GdSYhOjI (B:s (3GdbGgQI ,s (3OGQ GHf Gdbje ddfTQ hGdJhRjY,s (3OGQ GHf YaGf ddfTQ hGdJhRjY ,s, 2003)
(3GdYbjOI GdESdGejI(B.s
Keywords: (3Yde GdcdGes; (3YbjOIs